Focused crawling for automatic service discovery, annotation and classification in industrial digital ecosystems - Dong, Hai; Hussain, Farookh Khadeer (Institute of Electrical and Electronic Engineers, 2011)
Digital Ecosystems make use of Service Factories for service entities’ publishing, classification and management. However, before the emergence of Digital Ecosystems, there existed ubiquitous and heterogeneous service information in the Business Ecosystems environment. Therefore, dealing with the pre-existing service information becomes a crucial issue in Digital Ecosystems. This issue has not been addressed previously in the literature. In order to resolve this issue, in this paper we present a conceptual framework for a semantic focused crawler, with the purpose of automatically discovering, annotating and classifying the service information with the Semantic Web technologies. The technical and evaluation details of the framework are also presented and discussed in this paper.